Trichoderma, Truban@, Pythium, and lighting influence on carnation development and flowering - Graper, David F., author; Hanan, Joe J., advisor; Goldsberry, Kenneth L., committee member; Baker, Ralph, committee member (Colorado State University. Libraries, 1985)
Investigations were carried out on the merit of utilizing Trichoderma in the production of carnations. Two different strains of Trichoderma harzianum, T-12 and T-95 were used. The effectiveness of Trichoderma as a control agent against Pythium root rot was found to be small. Some alterations in carnation development were observed, but were insufficient to warrant recommending it use. Growth response as a consequence of Trichoderma were insignificant. If a soil-borne disease problem, such as Pythium root rot, does exist, Truban@ is recommended for control, as it was very effective in these experiments. Two experiments were conducted on photoperiodism and timing in the carnation. These were designed to determine if current carnation culture should be modified. Potential benefit was observed, for the grower, in the use of a long day treatment for an older crop of carnations, increasing production prior to a holiday demand period or a crop ' s removal from production. The use of a period of short days, prior to the long day period, was also investigated. Results were ambiguous, and no recommendations could be made.
Covers not scanned.
Keywords: Carnations -- Growth